Dare to lead: the transformation of bank of Baroda: a CEO's personal account of historic changes in a large corporation - Khandelwal, Anil K. (New Delhi, 2011)
Dare to Lead is the fascinating story of how Anil K. Khandelwal transformed Bank of Baroda (BOB) from being just another public sector bank into one of the most valuable brands in Indian banking.This is the story of the leadership challenges, management solutions and personal and professional excitement the author experienced in transforming the 97 year old bank into a modern, tech-savvy, customer-centric bank.This book is an excellent blueprint for undertaking transformation in large, geographically dispersed public sector enterprises. It describes how a large-sized bank was transformed on all parameters with clear vision, execution discipline, customer centricity and people engagement. The author emphasizes that large-scale transformation can be undertaken successfully only if the CEO shows courage to change the status quo and mobilize the human effort within the organization.The story of BOB's transformation has captured international attention and finds its mention in Harvard Business Review, Human Resources Development International and the book The India Way by the Wharton School faculty.
Keywords: Executive ability-India